Sistem Retensi Berkas Rekam Medis Di Rumah Sakit Ibu dan Anak (RSIA) Annisa Kota Pekanbaru - Nur' Aini; Andri Permana Wicaksono; M. Choirur Roziqin; Muhammad Yunus (Universitas Duta Bangsa Surakarta, 2022)
Medical record retention is an activity of reducing medical record files from storage shelves by determining the storage period for medical record files that are stored for at least 5 years since the patient was last treated or returned from treatment at the hospital. RSIA Annisa Pekanbaru City filing rack conditions are narrow and full so that officers have difficulty finding inactive files that are still in active shelves for retention by taking groups of medical record numbers to look for medical records that must be retained. In this case, the medical record retention process which is still manual, by recapitulating the medical record files that have been retained with the retention form recapitulation in this case can increase the workload of medical record officers because they have to spend their working time outside the shift to retain medical record files. The purpose of this study was to create a medical record file retention system at RSIA Annisa Pekanbaru City. Data collection techniques by interview, observation, documentation and FGD This type of research is qualitative using the waterfall method. Making a system using the PHP programming language and MySQL as the database, with admin lte as a template in this medical record file retention system. Testing this system using Black Box Testing. The results of this study are the medical record file retention system can facilitate the work of officers in doing retention by quickly finding files that have been inactive on the active shelf. As well as ensuring the storage of valuable medical record documents.